2020
DOI: 10.1177/1528083719900670
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the impact and post-impact behaviour of glass and glass/natural fibre hybrid composites made with various stacking sequences: Experimental and theoretical analysis

Abstract: In the present work, impact and post-impact response of thermoset composite laminates manufactured from glass, flax, jute fabrics and their hybrid combinations (glass/ jute and glass/flax) made with various stacking sequences was studied. The low-velocity impact response of these laminates was investigated by drop-weight impact tests at different energy levels (20-50 J). Additionally, their post-impact behaviour was studied by compression after impact tests, measuring their residual compressive strength. Impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 36 publications
(27 reference statements)
0
10
2
Order By: Relevance
“…When compared to the identical stacking arrangement using carbon and glass or basalt fibres, the placement of carbon layers as the core obtained the maximum energy absorption performance [ 141 ]. Impact studies revealed that natural or hybrid composites absorbed more impact energy than glass/epoxy composites due to substantial impact damages, according to Selver et al [ 150 ].…”
Section: Perforation Resistance Of Hybrid Compositementioning
confidence: 99%
“…When compared to the identical stacking arrangement using carbon and glass or basalt fibres, the placement of carbon layers as the core obtained the maximum energy absorption performance [ 141 ]. Impact studies revealed that natural or hybrid composites absorbed more impact energy than glass/epoxy composites due to substantial impact damages, according to Selver et al [ 150 ].…”
Section: Perforation Resistance Of Hybrid Compositementioning
confidence: 99%
“…The reinforcement material is very effective in defining the final impact properties of composites [24][25][26][27]. For this reason, as can be seen in Table 5, as the layers of reinforcement material in the composite structure change, the impact resistance values of the structure differ.…”
Section: Drop-weight Resistancementioning
confidence: 99%
“…13 Nevertheless, these laminates are particularly prone against delamination, which strongly reduces their properties such as the load-bearing capacity, compression strength, toughness, and fatigue life. 412 Therefore, the study to enhance the interlaminar fracture toughness of glass fibre laminates has drawn the attention of the designers and composites manufacturers. Delamination or inter-ply separation is the most predominant and crucial failure mechanism in composite laminates.…”
Section: Introductionmentioning
confidence: 99%